2010
DOI: 10.1211/jpp.62.04.0015
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effect of matrine on isoproterenol-induced cardiotoxicity in rats

Abstract: Our results suggest that matrine has a significant cardioprotection against isoproterenol-induced cardiotoxicity through its antioxidant property.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 17 publications
2
36
0
Order By: Relevance
“…These alkaloids have been found to show a variety of pharmacological activities, including anti‐inflammatory, ‐viral, ‐fibrotic, and ‐cancer properties. According to our and others’ previous studies, the antioxidative and cardioprotective activities of matrine were featured 18, 19, 20. Several previous studies indicated that matrine regulated some protein kinases, such as AMP‐activated protein kinase and Janus‐activated kinase 21, 22.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…These alkaloids have been found to show a variety of pharmacological activities, including anti‐inflammatory, ‐viral, ‐fibrotic, and ‐cancer properties. According to our and others’ previous studies, the antioxidative and cardioprotective activities of matrine were featured 18, 19, 20. Several previous studies indicated that matrine regulated some protein kinases, such as AMP‐activated protein kinase and Janus‐activated kinase 21, 22.…”
Section: Introductionmentioning
confidence: 75%
“…Matrine, oxymatrine, and sophocarpine are typical matrine‐type alkaloids extracted from S. flavescens exhibiting similar bioactive effects attributed to their comparable molecular structures. Matrine, oxymatrine, and sophocarpine were known as cardiovascular protective agents and showed potent antioxidant effects 20, 26, 34…”
Section: Discussionmentioning
confidence: 99%
“…Matrine can be obtained from plants of the Sophora genus and has always been used in traditional Chinese medicine to treat inflammation (10). Matrine has been shown to produce a wide range of pharmacological effects and has been used to treat a variety of diseases, including viral hepatitis, neuropathic pain and isoproterenol-induced heart disease (11)(12)(13). In addition, significant antitumor effects have been found in gastric cancer, rhabdomyosarcoma, acute myeloid leukemia and breast cancer (14,15), and studies have shown that matrine exhibits antioxidant effects in a number of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Although they are rarely mentioned, the anti-oxidant properties of matrine have been described in www.nature.com/aps Liu ZW et al Acta Pharmacologica Sinica npg previous studies [13] . Matrine treatment exerted therapeutic benefits in cardiac injury and cardiac dysfunction [14] , and also induced cardiomyocyte apoptosis in hyperglycemia; although the underlying mechanisms of matrine's cytoprotective effects remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%